1983
DOI: 10.1017/s0033291700050157
|View full text |Cite
|
Sign up to set email alerts
|

Can a computer take a psychiatric history?

Abstract: SynopsisA program on an inexpensive microcomputer was designed to elicit personal histories from patients in a general psychiatric ward. Their answers were compared with the information recorded by the responsible psychiatric team. Where answers disagreed with the clinicians' records, the patient was interviewed to investigate the discrepancy. In the computer-elicited case-histories 90% of items were correct; a further 3% of items were considered correct by the patient. Most patients' computer histories reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(44 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…And it is now well recognized that patients react favorably, even with enjoyment, to interviews that are carefully written [9,17]. But perhaps most important for our current study, patients have indicated to to us that they are sometimes more comfortable with a computer than they are with a doctor while answering questions about matters of a potentially embarrassing nature [12,17], and this has been corroborated by others [18][19][20][21][22].…”
supporting
confidence: 68%
“…And it is now well recognized that patients react favorably, even with enjoyment, to interviews that are carefully written [9,17]. But perhaps most important for our current study, patients have indicated to to us that they are sometimes more comfortable with a computer than they are with a doctor while answering questions about matters of a potentially embarrassing nature [12,17], and this has been corroborated by others [18][19][20][21][22].…”
supporting
confidence: 68%
“…Benefits for patients CAHTS can be used in several clinical settings and are particularly useful in eliciting potentially sensitive information, for example, on alcohol consumption, 29,30 psychiatric care, [31][32][33][34] sexual health 35 and gynaecological health. 36 Using CAHTS before the consultation would also, in principle, allow more time for the patient to discuss their actual health problem rather than routine aspects of medical history with their physician.…”
Section: 26-28mentioning
confidence: 99%
“…29 In another study, parents originally assumed that an interview using a computer was not as 'friendly and personal', but became more optimistic after the interview was completed. 31 …”
Section: Facilitating Delivery Of Care To Those With Special Needsmentioning
confidence: 99%
“…Patients have been required to interact with computers in many different situations, which included medical history taking (Slack, Hicks, Reed and Van Cura, 1966;Slack and Van Cura, 1968;Greist, Gustafson and Stauss, 1973;Lucas, Mullin, Luna and McIlroy, 1977;Fitter and Cruickshank, 1982;Carr, Ghosh and Ancill, 1983), behavioral assessment (Carr and Ghosh, 1983a), and psychiatric assessment (Lewis, Pelosi, Glover, Wilkinson, Stansfeld, Williams and Sheperd, 1988;Wright, 1990). Various justifications have been offered in these previous studies for using computer-based methods to achieve certain clinical objectives, ranging from pressures of short appointment times and differing abilities of individual doctors (Wright, 1990) that may result in failure to detect problems, to shortage of experienced staff and limited availability of treatment to patients in areas away from appropriate treatment centers (Carr and Ghosh, 1983a).…”
Section: Human-computer Interactionmentioning
confidence: 99%
“…Nevertheless, there seems to be a broadly held conviction that behavioral and emotional malfunctioning constitutes a problem of a considerable prevalence (e.g., Sines, 1980). Existing therapeutic procedures often require the expertise and the actual involvement of specialist therapists and lengthy durations of management (Carr and Ghosh, 1983b;Carr, Ghosh and Ancill, 1983). This situation effectively has meant the restriction of such expertise to specialist behavioral units, out of reach of many sufferers (Carr and Ghosh, 1983b), as well as long client waiting lists.…”
Section: Human-computer Interactionmentioning
confidence: 99%